Comparisons of biophysical properties and bioactivities of mono-PEGylated endostatin and an endostatin analog - Wang, Shan (Chin J Cancer, 2016)
BACKGROUND: Endostatin (ES) is a well-established potent endogenous antiangiogenic factor. An ES variant, called zinc-binding protein-ES (ZBP-ES), is clinically available; however, its use is limited by rapid renal clearance and short residence time. PEGylation has been exploited to overcome these shortcomings, and mono-PEGylated ES (called M(2)ES) as well as mono-PEGylated ZBP-ES (MZBP-ES) are developed in our study. This study aimed to compare the biophysical properties and biological effects of M(2)ES and MZBP-ES to evaluate their druggability. METHODS: Circular dichroism and tryptophan emission fluorescence were used to monitor the conformational changes of M(2)ES and MZBP-ES. Their resistance to trypsin digestion and guanidinium chloride (GdmCl)-induced unfolding was examined by Coomassie staining and tryptophan emission fluorescence, respectively. The biological effects of M(2)ES and MZBP-ES on endothelial cell migration were evaluated using Transwell migration and wound healing assays, and the uptake of M(2)ES and MZBP-ES in endothelial cells was also compared by Western blotting and immunofluorescence. RESULTS: Structural analyses revealed that M(2)ES has a more compact tertiary structure than MZBP-ES. Moreover, M(2)ES was more resistant to trypsin digestion and GdmCl-induced unfolding compared with MZBP-ES. In addition, although M(2)ES and MZBP-ES showed comparable levels of inhibiting transwell migration and wound healing of endothelial cells, M(2)ES displayed an increased ability to enter cells compared with MZBP-ES, possibly caused by the enhanced interaction with nucleolin. CONCLUSIONS: M(2)ES has a more compact tertiary structure, is more stable for trypsin digestion and GdmCl-induced unfolding, exhibits increased cellular uptake and shows equivalent inhibitory effects on cell migration relative to MZBP-ES, indicating that M(2)ES is a more promising candidate for anticancer drug development compared with MZBP-ES.